OAUNI photometry of SN 2024iss - Pereyra, Antonio (2024)
We report photometry of Type II SN 2024iss gathered with the OAUNI 51cm telescope at Huancayo Observatory, Peru. CCD imaging in R filter was performed on three consecutive nights under non-photometric conditions with airmasses lower than 1.5. The integration time was 70x20s=1400s in each observation. Our measurements yielded: Date (UT) | filter | seeing (") |mag, 2024-06-07.102 | R | 2.6 |13.40 +/- 0.02, 2024-06-08.093 | R | 2.6 | 13.49 +/- 0.02, 2024-06-09.094 | R | 2.8 | 13.59 +/- 0.02. UCAC4 field stars were used for the zero point calibration. Our observations are ~3.7 weeks after the GOTO detection. The OAUNI project is supported by UNI, TWAS, IGP and ProCiencia-Concytec (Convenio 133-2020 Fondecyt).